Ratcheting fatigue failure of a carbon steel pipe tee in a nuclear power plant using the deformation angle. (August 2020) - Kim, Sung-Wan; Jeon, Bub-Gyu; Hahm, Dae-Gi; Kim, Min-Kyu
Highlights: A leakage line was examined using the relationship between the moment and deformation angle of a 3-in. carbon steel pipe tee. Low-cycle fatigue curves were presented for the moment and deformation angle of a 3-in. carbon steel pipe tee. A low-cycle fatigue curve was presented for the ratcheting deformation angle of a 3-in. carbon steel pipe tee. Abstract: Among the many facilities constituting nuclear power plants, piping is a significant facility that handles the transport of fluids, such as steam and cooling water. These pipes can be exposed to external forces, such as fluid, mechanical vibrations, pressure, wind, and earthquakes. In particular, damage to major piping can cause a loss-of-coolant accident (LOCA), which is a serious accident in nuclear power plants, along with radioactivity leakage. Among the components of piping, elbows and tees are elements vulnerable to earthquakes because the nonlinear behavior caused by earthquakes can be concentrated at these points, and the major failure mode is leakage due to ratcheting fatigue. In this study, for the 3-in. carbon steel pipe system used in nuclear power plants, the limit state of a tee was defined as the leakage caused by a through-wall crack, and an in-plane cyclic loading test was conducted. A leakage line and low-cycle fatigue curves were presented using the relationship between the moment and deformation angle of the tee. Moreover, this paper reports the low-cycle fatigue curve of the ratcheting deformation angle capable of expressing the leakage caused by ratcheting fatigue, which is the major failure mode of the tee. As it is difficult to measure the moment and deformation angle using conventional sensors, the nonlinear behavior of the tee deformed by external forces was measured using an image measurement system.